Óxidos de ferro dopados com vanádio ou nióbio como catalisadores em reações de oxidação - Henrique dos Santos Oliveira (2013)
Iron oxides doped with vanadium or niobium were obtained by coprecipitation method in a solution of sodium hydroxide. The oxides were subjected to a treatment with H2O2 to generate "peroxos" groups on their surface, highly oxidizing , allowing the application as heterogeneous catalysts in oxidation reactions. Results of X ray diffraction (XRD) showed that both niobium and vanadium were introduced into the structure of the iron oxide . The oxides were also characterized using Mössbauer spectroscopy, scanning electron microscopy (SEM) and transmission (TEM) both coupled to the detector of energy dispersive of X-ray (EDS), and adsorption / desorption of N2. The characterization techniques indicate the formation of hematite and maghemite as crystalline phases, while the doping element influence both the type of oxide formed as the specific area of the material. After incorporation of V, the specific area increased from 75 m2 g-1 (pure hematite) to 104 m2 / g, and the presence of Nb resulted in a material 117 m2 g-1. The oxides were evaluated as catalysts in advanced oxidation processes such as heterogeneous Fenton and photocatalysis, using the pollutant organic methylene blue dye as template. . The presence of Nb or V affect significantly influenced the removal the dye (approximately 70%), whereas the pretreatment with H2O2 improved the removal capacity of the dye by the catalyst containing Nb, probably due to the oxidant "peroxos" groups formed on the catalyst surface.